Metal Catalyzed Carboxylative Coupling of Terminal Alkynes, Organohalides and Carbon Dioxide: A Novel and Promising Synthetic Strategy Toward 2-Alkynoates (A Review) - Vessally, Esmail; Hosseinian, Akram; Babazadeh, Mirzaagha; Edjlali, Ladan; Hosseinzadeh-Khanmiri, Rahim (Current Organic Chemistry, 2018)
2-Alkynoates are important unsaturated carbonyl compounds showing a large application as intermediates in organic synthesis. Despite wide importance of these compounds in synthetic chemistry, very few synthetic methods have been reported till date. In recent years much effort has been made to develop the carboxylative coupling of terminal alkynes, organohalides and carbon dioxide to provide the 2-alkynoate derivatives. Good yields, high atom and step economy, and readily available substrates are the key features of this page of 2-alkynoate synthesis. This review article is an attempt to survey literature describing synthetic methods for the preparation of 2-alkynoate derivatives through the three-component reaction of terminal alkynes, organohalides and CO2.
Keywords: carboxylative coupling